Chinese herbal injections combined with EGFR-TKIs for intervention of non-small cell lung cancer: a systematic review and meta-analysis - Yuan, Zichun; Yan, Mei; Wu, Tongtong; Zhang, Ganlin; Yang, Guowang; Wang, Xiaomin (Frontiers in Pharmacology, 2025)
ObjectiveTo serve as a clinical reference, we conducted a meta-analysis to assess and compare the efficacy and safety of combining Chinese herbal injections (CHIs) with epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) for treating advanced EGFR-mutated non-small cell lung cancer (NSCLC).MethodsPredetermined databases contained randomized controlled studies comparing CHIs + EGFR-TKIs to EGFR-TKIs alone. The Cochrane Reviewer’s Handbook for Systematic Reviews of Interventions was used to evaluate study methodology. To assess the effects of CHIs on patients with NSCLC receiving EGFR-TKIs, R (version 4.4.0) and RevMan (version 5.4) were used to conduct a meta-analysis using the Mantel–Haenszel or Inverse Variance method. The quality of results was evaluated using the Grade of Recommendations Assessment, Development and Evaluation (GRADE) method.ResultsThe 13 qualifying trials included 899 subjects. The objective response rate (ORR) was significantly increased by Kanglaite injection (RR = 1.52, 95% confidence interval [CI]: 1.07–2.15, p = 0.02). The disease control rate (DCR) was influenced by Kanglaite injection (RR = 1.14, 95% CI: 1.01–1.29, p = 0.04) and Aidi injection (RR = 1.23, 95% CI: 1.02–1.48, p = 0.03). Shenmai injection + EGFR-TKIs reduced dermatologic toxicities (RR = 0.35, 95% CI: 0.18–0.69, p = 0.002). The combination of CHIs with EGFR-TKIs improved the expression of CD3+ (standardized mean difference [SMD] = 1.38, 95% CI: 0.46–2.30, p = 0.003), CD4+ (SMD = 1.08, 95% CI: 0.51–1.65, p = 0.0002), and the CD4+/CD8+ ratio (SMD = 0.96, 95% CI: 0.54–1.38, p < 0.00001) compared to EGFR-TKIs alone. The GRADE method revealed that most outcomes exhibited low certainty evidence.ConclusionThe combination of CHIs and EGFR-TKIs improved ORR, DCR, adverse effects, and immune function in patients with NSCLC. Due to limitations in the assessed research, high-quality clinical studies with rigorous designs are required to confirm the findings.Systematic Reviewhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024561845, Identifier CRD42024561845.